Senarai pemikiran Sulistyo Basuki : profesor pertama ilmu perpustakaan dan informasi di Indonesia - Senarai_pemikiran_Sulistyo-Basuki_:_profesor_pertama_ilmu_perpustakaan_dan_informasi_di_Indonesia (ISIPPI, 2014)
wt,3./ws.c.1-3